Between PONA and Netizen The Spectrum of Adoption Levels in Network Era - sheiful yazan (Al-Hikmah: Jurnal Dakwah dan Ilmu Komunikasi, 2005)
Internet is an innovation. This invention can not be rejected any more. Adopting is something natural that should be happened in every society. There aremany levels of adopting of innovation in a society. Among internet adopter, netizen is an early adopter and PONA is not adopted yet. All categories are object of Dakwah. This article discusses the Dakwah task for both categories, the adopter and the prospective adopter